2016
DOI: 10.7575/aiac.ijalel.v.5n.5p.6
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Three Kinds of Reading Strategies on EFL Learners’ Reading Comprehension and Gender Difference Using Think-aloud Protocol

Abstract: Reading comprehension strategy instruction is a powerful tool in teaching context. The present study examines the effect of teaching three kinds of reading strategies on L2 learners' reading comprehension ability as well as identifying the gender role in this intervention. This quasi experimental study was carried out on 100 Iranian EFL students who were chosen on the basis of a convenient sampling procedure. These participants were divided into two groups of experimental and control. 50 students (experimental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 13 publications
0
4
1
Order By: Relevance
“…It can be noticed that though there was no significant difference between male and female students' reading comprehension performance after strategy instruction, male students seemed more benefited from the training compared to females. This result is in contrast to the study conducted by Karizak and Khojasteh [61].…”
Section: Results Of Reading Comprehensioncontrasting
confidence: 99%
See 1 more Smart Citation
“…It can be noticed that though there was no significant difference between male and female students' reading comprehension performance after strategy instruction, male students seemed more benefited from the training compared to females. This result is in contrast to the study conducted by Karizak and Khojasteh [61].…”
Section: Results Of Reading Comprehensioncontrasting
confidence: 99%
“…In fact, there have been inconsistencies in results about strategy training and gender. According to Karizak and Khojasteh [61], while some researchers found no significant differences between male and female students in reading ability or RSU after RSs training, other studies found that women outperform males at one time and males did better at other times. They also underlined that there are "gender-oriented texts" which are yardsticks for males' and females' choice of learning strategies.…”
Section: Conclusion Limitations and Recommendationsmentioning
confidence: 99%
“…Many studies have shown that the use of reading strategies has a significant effect on students' reading comprehension. In addition, male students use more reading strategies than female students and perform better in reading comprehension (Karizak & Khojasteh, 2016) as well as students optimally use time to read and understand the text better (Ulu & Ulusoy, 2019), and from these results a thought-speech protocol was generated where mental strategies and processes were developed in different ways (Bulut & Ertem, 2021) As they showed a high significant difference in the levels of comprehension of texts by study groups (Li et al, 2022) despite the student deficiencies since when encouraging the use of strategies it should be taught explicitly to find findings that involve teachers and students (Brevik, 2019), it is for this reason that teacher development As a tutor he is very important in guiding reading strategies as the development of skills and critical thinking to transform students into skilled readers (Tiba, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…eing a good reader implies decoding the text and its correct understanding, to achieve this it is necessary to apply a strategic reading since the scientific literature indicates that the use of multiple reading strategies generates better results in terms of reading comprehension (Moir et al, 2020), in addition, reading, by nature leads to the understanding of texts and plays a fundamental role during the learning process and the acquisition of knowledge (Deri & Shamsudin, 2018), therefore, it is vitally important to use reading strategies when reviewing academic information (Cogmen & Saracaloglu, 2009). Good reading comprehension is the basis for correct academic performance and yet many students worldwide lack it (Elston et al, 2022), so for some decades it has been believed that primary and secondary school teachers should include reading techniques or strategies within their instruction plans (Wilson-Lopez et al, 2016), given that instruction on reading comprehension strategies by teachers towards students is an effective tool In the learning process (Karizak & Khojasteh, 2016), likewise, the teaching of reading strategies by teachers is a great support for students when developing reading and text comprehension skills (Varga, 2017), additionally, there is solid evidence of the improvement in the grades of students who employ reading strategies (Ulu & Ulusoy, 2019). Instruction in reading strategies is recognized as a fundamental pillar for the development of literacy and reading programs, therefore, in many countries time has been invested in improving the teaching of these strategies at different levels of academic training (Al Khaiyali, 2014), in turn, there are studies that affirm that metacognitive reading strategies are more used than general reading strategies (Rianto, 2022), However, most studies on the subject associate the use of reading strategies with students' high reading comprehension performance (Garcia y Benitez, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…It was first proposed by Newell & Simon (1972) to evaluate learners' comprehension. A wide range of scholars have discussed the concept of Think-Aloud strategy implementation in teaching English as EFL (Ness, 2015(Ness, , 2016(Ness, , 2015Lin & Yu, 2015;Karizak & Khojasteh, 2016;Dj & Ali, 2015;Chimics, 2015;Carioli & Peru, 2016;Bai, 2018;Afifah, 2017). For Siagian & Katemba (2016), Think-Aloud is the verbalization of learners' actual thoughts while they read.…”
Section: Literature Reviewmentioning
confidence: 99%